Impact of cigarette smoke and aerobic physical training on histological and molecular markers of prostate health in rats - Veras, A. S.C. [UNESP]; Baptista, D. B. [UNESP]; Dos Santos, N. J.; Thorpe, H. H.A.; Seraphim, P. M. [UNESP]; Neto, A. R. Florido; Teixeira, G. R. [UNESP] (FapUNIFESP (SciELO), 2020)
Recent evidence suggests that aerobic physical training may attenuate the deleterious effects of cancer risk factors, including smoking. We investigated the effects of cigarette smoke inhalation and aerobic physical training on the expression of steroid receptors and inflammatory and apoptotic proteins in the prostate. Forty male Wistar rats were distributed in four groups: control (CO), exercise (EXE), cigarette smoke exposure (CS), and cigarette smoke exposure with exercise (CS+EXE). For eight weeks, animals were repeatedly exposed to cigarette smoke for 30 min or performed aerobic physical training either with or without the cigarette smoke inhalation protocol. Following these experiments, we analyzed prostate epithelial morphology and prostatic expression of androgen (AR) and glucocorticoid receptors (GR), insulin-like growth factor (IGF-1), B-cell lymphoma-2 (BCL-2), BCL-2-associated X protein (BAX), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and nuclear factor-kappa B (NF-κB) via immunohistochemistry. Cigarette smoke exposure stimulated the expression of AR, IGF-1, BCL-2, and NF-κB while downregulating BAX, IL-6, and TNF-α labeling in the prostate. In contrast, aerobic physical training attenuated cigarette smoke-induced changes in AR, GR, IGF-1, BCL-2, IL-6, TNF-α, and NF-κB. This suggests that cigarette smoke stimulates inflammation and reduces apoptosis, culminating in increased prostatic epithelial and extracellular matrices, whereas physical training promoted beneficial effects towards maintaining normal prostate morphology and protein levels.
Keywords: Androgen receptor; BAX; BCL-2; Endurance exercise; Growth factors; Inflammation